Relationship between periodontitis and Alzheimer's disease: A Narrative Literature Review: Relación entre periodontitis y enfermedad de Alzheimer: Una revisión narrativa - James-Gómez, Sarai Michelle (2024)
Introduction: With the increasing aging of the population as a global demographic phenomenon, it is expected that some of the most prevalent pathologies in these ages will become more frequent, including Alzheimer's disease (EA) and periodontal disease. For some years, experts in the field have identified a potential relationship between both entities, which shows the need to perform an analysis of the biological variables related and eventually involved. Objective: The aim of this work is to describe the relationship between periodontopathogenic bacteria and Alzheimer's disease. Methods: Various scientific review articles that were part of the study were incorporated, selected from journals such as SciELO, PubMed, EBSCO and Redalyc. This literary review article examines the documented evidence on the statistical relationship between Alzheimer's and periodontal disease, considering its possible etiopathogenesis. A bibliographic search was carried out on this topic. Results: A relationship was found between periodontopathogenic bacteria and Alzheimer's disease. Conclusions: It is important to highlight that further studies are needed to identify the causal association between both diseases. From the etiopathogenesis paradigm, there are compelling reasons to suspect the existing link.